Assessment of self-health management capacity and its influencing factors in patients with decompensated liver cirrhosis in Shanxi Province, China - Li, Feixue; Wang, Jing; Wen, Hongping (Frontiers in Public Health, 2025)
ObjectiveThis research aimed to evaluate the current status of self-health management capacity among patients with decompensated hepatic cirrhosis in Shanxi Province, China, and to analyze its influencing factors.MethodsA questionnaire survey was performed from October 2024 to February 2025 at Shanxi Provincial People’s Hospital, targeting patients with decompensated liver cirrhosis. Self-developed questionnaires were employed to measure self-health management capacity and identify associated influencing factors.ResultsA total of 460 valid responses were collected. The scale demonstrated excellent internal consistency reliability, with a Cronbach’s alpha of 0.94, and each dimension’s Cronbach’s alpha ranged from 0.78 to 0.90. The overall construct validity, indicated by the KMO was 0.93, with individual dimension KMO values between 0.68 and 0.88. The average score of self-health management ability was 3.04 ± 0.51 out of 5. Correlation analysis showed that cognitive ability, psychological status, behavioral lifestyle, and treatment adherence had very strong positive correlations with overall self-management capacity (0.8 < r ≤ 1, p < 0.001). The multiple linear regression model yielded an R-squared value of 0.687 (p < 0.001). Multivariate analysis indicated that higher educational attainment, increased household income, and longer disease duration were significantly positively associated with self-management scores (positive Beta coefficients, p < 0.05). Conversely, occupational status, healthcare burden, alcohol consumption history, comorbidities, and Child-Pugh classification were significantly negatively associated with self-management capacity (negative Beta coefficients, p < 0.05).ConclusionThe self-health management capacity among patients with decompensated liver cirrhosis in Shanxi Province is moderate to low, influenced by various determinants such as education level, occupational status, monthly household income, healthcare burden, duration of liver cirrhosis, alcohol consumption history, comorbidities, and Child-Pugh classification. It is recommended a precise intervention strategy is proposed to enhance the public health prevention and control effect of liver cirrhosis: transitioning from traditional hospital-centric models to a stratified, intelligent, and community-integrated comprehensive prevention and control system.